2023
DOI: 10.30935/ojcmt/13365
|View full text |Cite
|
Sign up to set email alerts
|

Effects of social networking sites on university students’ academic performance: A systematic review

Abstract: This paper analyzed the effects of social networking sites (SNS) on university students’ academic performance. In this study, the peer-reviewed articles were taken from the SCOPUS database. The 22 articles meeting the inclusion criteria were involved in the analysis. Two researchers analyzed the articles using the content analysis method according to the researchers’ established analysis criteria. The results showed that research has generally reported positive and significant results on the influence of SNS o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 38 publications
0
1
1
Order By: Relevance
“…The results regarding the relationship between social media usage and GPA are inconsistent with previous research, which found that social media negatively impacts students' GPA (Junco & Cotton, 2012;Junco et al, 2010;Kalam et al, 2023;Karpinski et al, 2013;Masalimova et al, 2023;Yeboah & Ewur, 2014). For example, according to Shen's (2019) research, there is a negative correlation between the amount of time students spend on social media and their learning time and cumulative GPA.…”
Section: Discussioncontrasting
confidence: 96%
See 1 more Smart Citation
“…The results regarding the relationship between social media usage and GPA are inconsistent with previous research, which found that social media negatively impacts students' GPA (Junco & Cotton, 2012;Junco et al, 2010;Kalam et al, 2023;Karpinski et al, 2013;Masalimova et al, 2023;Yeboah & Ewur, 2014). For example, according to Shen's (2019) research, there is a negative correlation between the amount of time students spend on social media and their learning time and cumulative GPA.…”
Section: Discussioncontrasting
confidence: 96%
“…In their study, Masalimova et al (2023) conducted a comprehensive analysis of the impact of SNS on the academic performance of university students. A total of 22 articles were subjected to analysis.…”
Section: Introductionmentioning
confidence: 99%